Marcas toponímicas em solo piauiense: seguindo as trilhas das águas - Marcelo Alessandro Limeira dos Anjos (2012)
This research worked with a total corpus of 2881 Hydronyms, divided into two types of sources, preterite (the Description of Piauí, three old letters and one old map), with 176 Hydronyms; and contemporary, with 2705. In order to classify Hydronyms constrant in contemporary sources, the study selected the Southeast and Southwest mesoregions of the state of Piauí and their respective microregions, given their historical contribution to colonize the state. The classification of Hydronyms, in elements of Physical and Anthropocultural Nature, was done with basis on DICKs (1992a) taxonomic proposal. With this classification at hand, the study aimed to establish motivational patterns for both preterite and contemporary sources. It also tried to establish a correlation between phytogeographic and toponymical areas by analyzing the occurrence of the Toponym Buriti in both mesoregions. Some linguistic examples were also listed, especially those constant in older sources, so as to, in comparison with contemporary sources, point out cases in which there were orthographical variation, phonetic changes and partial or complete disuse of the Toponym. As a consequence of the very Analysis of the object of this research (Hydronyms), it was proposed to expand the classification of the elements of hydrotoponyms. The overall result of Dicks (1992a) taxonomic proposal allowed us to revise the element of numero-toponyms and chrono-toponyms. Given the high occurrence of toponymical syntagmas with the preposition OF, in contemporary data, the study tried to discuss such structures in correlation with the attribution of semantic roles, which, in its turn, allowed for both dialogue with the local Social History and the assumption of four groups which show semantic roles found in this Analysis. It was possible to observe, in the case of the preterite sources, that the most recurring elements of Physical Origins were Zoo and Hidro, which suggests a Zoological and Hydrological pattern for these first sources. In the first and the second preterite sources, but already with a decrease in the latter, it was possible to observe, in the case of elements with Anthropocultural Nature, the significant occurrence of the element Hagio. In the contemporary sources, in the case of elements of Physical Nature, for all microregions and both mesorregions, the element Fito was most common, where it is possible to see a change from the zoological and hydrological pattern of the preterite sources to a phytological pattern of current sources. Still on contemporary sources, the reaction to the frequence of the element Hidro, for instance, occurred in different ways in both mesoregions and also between microregions in the same mesoregion (Southwest). In this one, there seems to be to groups that differ, especially regarding the occurrence of the element Hidro, that is, in most southern regions (Alto Média Gurgueia, Alto Parnaíba and Chapadas do Extremo Sul), those in which the presence of large streams of water, especially in the first and the second regions aforementioned, and in those where the climate differs from what is found in the Southeast mesoregion, the occurrence of the element Hidro is the second most frequent. On the other hand, in the other three mocro-regions of the Southwest mesoregion (Floriano, Bertolínia and São Raimundo Nonato), the occurrence of the element Hidro has many more similarities to what is found for the three microregions of the Southeast mesoregion (Picos, Pio IX and Alto Médio Canindé). Taking these considerations into account, it is worth to reaffirm the importance of toponymical studies for the recovery and maintenance of the modus vivendi of the peoples who have recorded, in physical and human events, their peculiar view of the world. Such view, retrieved by the Analysis of old as well as contemporary letters and maps, can be expressed by the distribution of elements with Physical and Anthropocultural Nature, which may set certain motivational patterns of a certain age. Such patterns, in the light of Social History, evidence different historical and ideological aspects concerning naming places. It is worth to point out, finally, the importance of regional studies like this for future onomastic and toponymical mapping of the Brazilian territory, in its various local and regional manifestations.